2011
DOI: 10.1001/jama.2011.1692
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Tumor Necrosis Factor-α Antagonists and the Risk of Hospitalization for Infection in Patients With Autoimmune Diseases

Abstract: Context Although tumor necrosis factor alpha (TNF-α) antagonists are increasingly used in place of non-biologic comparator medications, their safety profile remains incomplete. Objectives To determine whether initiation of TNF-α antagonists compared with non-biologic comparators is associated with an increased risk of serious infections. Design, setting and patients Within a US multi-institutional collaboration, we assembled retrospective cohorts (1998–2007) of patients with rheumatoid arthritis (RA), infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
247
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 323 publications
(286 citation statements)
references
References 51 publications
23
247
1
6
Order By: Relevance
“…Recently, some reports have described LD in patients receiving TNF-α inhibitors [22][23][24] and the relative risk for LD in patients treated with TNF-α inhibitor was between 16.5 and 21 compared to that for the overall population [22]. Although our patients received methotrexate and some reports described that the incidence of serious infections in patients with TNF-alpha inhibitor was not significantly higher than those with disease modifying anti-rheumatic drugs (DMARDs) [35,36], two in vivo studies have reinforced the notion of an increasing risk for LD among patients receiving TNF-α inhibitors. First, the administration of a TNF-α-neutralizing antibody to mice in vivo inhibited TNF-α activity and resulted in enhanced L. pneumophila growth in the mouse lung [37].…”
Section: Discussionmentioning
confidence: 83%
“…Recently, some reports have described LD in patients receiving TNF-α inhibitors [22][23][24] and the relative risk for LD in patients treated with TNF-α inhibitor was between 16.5 and 21 compared to that for the overall population [22]. Although our patients received methotrexate and some reports described that the incidence of serious infections in patients with TNF-alpha inhibitor was not significantly higher than those with disease modifying anti-rheumatic drugs (DMARDs) [35,36], two in vivo studies have reinforced the notion of an increasing risk for LD among patients receiving TNF-α inhibitors. First, the administration of a TNF-α-neutralizing antibody to mice in vivo inhibited TNF-α activity and resulted in enhanced L. pneumophila growth in the mouse lung [37].…”
Section: Discussionmentioning
confidence: 83%
“…Even after extensive world-wide experience with anti-TNF-therapy in IBD and other indications, such as rheumatological or dermatological diseases, there still is some uncertainty about potential risks [9][10][11][12][13] . In the last few years, there has been an increasing trend towards an earlier introduction of TNF-inhibitors (which is associated with a better efficacy 14 ) either via a rapid step up 15,16 or top down 17 , to avoid prolonged steroid exposure and minimizing CDassociated morbidity and the need for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using administrative data have observed increased risk of serious infection, even with low doses of corticosteroid. 21,22 We observed declining use of prednisone during the study period; however, this decline was not linked to a reduction in the rates of pneumonia and opportunistic infection. A difference between this and earlier studies was the design; we did not compare prednisone users with nonusers, which is subject to bias by disease severity, but rather examined changes in both prednisone use and infection risk over time in the population of users and nonusers.…”
Section: Original Research and Contributionsmentioning
confidence: 76%